2017
DOI: 10.18632/oncotarget.23157
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin gene polymorphisms in Chinese Han population with breast cancer, a case-control study

Abstract: Cytokines are known as important regulators of the cancer involved in inflammatory and immunological responses. This fact and plethora of gene polymorphism data prompted us to investigate IL1 gene polymorphisms in breast cancer (BC) patients. Totally, 530 patients with BC and 628 healthy control women were studied. The genetic polymorphisms for IL1 were analyzed by Massarray Sequencing method. Three single nucleotide polymorphisms (SNPs) identified in IL1B, IL1R1 gene are thought to influence breast cancer ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Nine articles that included 11 case-control studies, with 4801 cases and 6116 controls, were identified for the meta-analysis (Landvik et al, 2009;Andersen et al, 2013;Kutikhin et al, 2014;Li et al, 2015;Wang et al, 2017Wang et al, , 2019aEaton et al, 2018;Qian et al, 2018;Zuo et al, 2018). Because of studying three types of cancer, the article by Kutikhin et al (2014) was separated into three independent studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine articles that included 11 case-control studies, with 4801 cases and 6116 controls, were identified for the meta-analysis (Landvik et al, 2009;Andersen et al, 2013;Kutikhin et al, 2014;Li et al, 2015;Wang et al, 2017Wang et al, , 2019aEaton et al, 2018;Qian et al, 2018;Zuo et al, 2018). Because of studying three types of cancer, the article by Kutikhin et al (2014) was separated into three independent studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, linkage disequilibrium patterns in different ethnicities may be a possible reason for this phenomenon (Wu et al, 2015). It should be noted that the control groups in three articles (Kutikhin et al, 2014;Zuo et al, 2018;Wang et al, 2019a) were inconsistent with the HWE. Thus, we BC, breast cancer; CRC, colorectal cancer; GC, gastric cancer; HB, hospital-based; HWE, Hardy-Weinberg equilibrium; LC, lung cancer; MAS, mass array system; NSCLC, nonsmall-cell lung cancer; OC, ovarian cancer; PB, population-based; RCC, renal cell carcinoma; RFLP-PCR, restriction fragment length polymorphism-polymerase chain reaction; RT-PCR, real-time polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 98%
“…However, association studies indicated that rs4851527 was associated with decreased risk of tuberculosis (Ren et al, ) and ankylosing spondylitis (Xia et al, ). No significant association was found between the two SNPs (rs3218896 and rs2072472) and risk of IgA nephropathy (Xie et al, ), tuberculosis (Ren et al, ), and breast cancer (Zuo et al, ). Moreover, no significant association was also found between rs2072472 and the risk of ankylosing spondylitis (Xia et al, ) and endometriosis (Chun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The minor allele of rs10490571 was associated with an increased risk of immunoglobulin (Ig)A nephropathy and breast cancer in previous studies . Although rs956730 has been investigated in association studies on hand osteoarthritis, knee osteoarthritis and breast cancer, none of these studies showed any significant association between rs956730 and the risk of disease. Rs3917225 was reported to have no correlation with the location of papillary thyroid carcinoma in a Korean population .…”
Section: Discussionmentioning
confidence: 99%